(3fbO GdQLGds - (3GdJaQjTj , eUWaj Hf GdMSjf GdMSjfj,J (B1030 (3g` s
(3ChdgG (B:s
(3CeG HYO Efg dGTc hdG GQJjGH ai Cf Yde GdMOjK hGdBKGQ ef CTQa GdYdhe GdESdGejI bOQkG hGdMce HUMI GdCMGOjK hVYagG ehbha Ydi GdYde HCMhGd GdQLGd s
(3BNQgG (B:s
(3hjMSf JQJjH GdHdO GdKGfi HKe hHbQjI HdO fGMjI Ebdje , hfSH Edi CjgG TGA JeJ GdQSGdI s
(3hedMb HgG efXheI aj Gdabgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B232 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B247s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B411 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B572 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B460 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdOcJhQ MSjf Ydj eMahX (B((3HZOGO (B25) s
Keywords: (3GdJGQjNs